2012
DOI: 10.4049/jimmunol.1102680
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Mesoangioblasts Require Macrophage IL-10 for Survival in a Mouse Model of Muscle Injury

Abstract: The aim of this study was to verify whether macrophages influence the fate of transplanted mesoangioblasts—vessel-associated myogenic precursors—in a model of sterile toxin-induced skeletal muscle injury. We have observed that in the absence of macrophages, transplanted mesoangioblasts do not yield novel fibers. Macrophages retrieved from skeletal muscles at various times after injury display features that resemble those of immunoregulatory macrophages. Indeed, they secrete IL-10 and express CD206 and CD163 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 98 publications
1
48
0
Order By: Relevance
“…75 'Alternatively activated' or 'M2' macrophages predominate during the resolution phases of the damage when they regulate the termination of the inflammatory responses. 69,76 Monocyte-derived macrophages undergo dynamic transitions between M1 and M2 and this timely transition is increasingly felt to be the key to muscle homeostasis. 77,78 MAP kinase phosphatase-1 (MKP-1) regulates cell remnant disposal, macrophage transition and muscle healing.…”
Section: The Predators: Macrophages Scavenge Muscle Debrismentioning
confidence: 99%
See 1 more Smart Citation
“…75 'Alternatively activated' or 'M2' macrophages predominate during the resolution phases of the damage when they regulate the termination of the inflammatory responses. 69,76 Monocyte-derived macrophages undergo dynamic transitions between M1 and M2 and this timely transition is increasingly felt to be the key to muscle homeostasis. 77,78 MAP kinase phosphatase-1 (MKP-1) regulates cell remnant disposal, macrophage transition and muscle healing.…”
Section: The Predators: Macrophages Scavenge Muscle Debrismentioning
confidence: 99%
“…Conversely, muscle stem cells influence macrophages. This is the case for vessel-associated muscle stem cells (also referred to as mesoangioblasts), myogenic precursors that express pericyte markers and cross vessel walls; 69,93,94 they sustain the ability of macrophages to clear apoptotic cells and promote the expression of genes associated with their alternative activation. 95 …”
Section: The Predators: Macrophages Scavenge Muscle Debrismentioning
confidence: 99%
“…Cardiotoxin (50 ml, 10 mM; Sigma-Aldrich, Germany) has been injected into tibialis anterior (TA) muscles, and damage and regeneration assessed as described (24,25). When indicated, BoxA (10 mg/TA; HMGBiotech, Milan, Italy) has been coinjected with cardiotoxin and the treatment repeated every other day.…”
Section: Sterile Injurymentioning
confidence: 99%
“…Mesoangioblasts are a population of stem cells associated with the walls of the microvasculature in skeletal muscle that can contribute to regeneration (Sampaolesi et al, 2003). When mesoangioblasts were transplanted into muscle that had been injured by CTX injection, their differentiation was significantly reduced when IL-10 signaling was blocked by an IL-10 receptor (IL-10R)-neutralizing antibody (Bosurgi et al, 2012). Similarly, culturing mesoangioblasts in the presence of M2 macrophages increased the differentiation of mesoangioblasts into myotubes, an effect that was blocked by antibodies to IL-10R.…”
Section: Role Of Ifnγ-mediated Signalingmentioning
confidence: 99%
“…In addition, muscle cells themselves have the capacity to express at least two cytokines, IFN and IL-4, that can modulate their own regeneration through an autocrine route. Development (2014Development ( ) doi:10.1242 or myogenic cells (Villalta et al, 2011), recent findings demonstrated that macrophage-derived IL-10 can affect muscle regeneration by promoting mesoangioblast differentiation into the myogenic lineage (Bosurgi et al, 2012). Mesoangioblasts are a population of stem cells associated with the walls of the microvasculature in skeletal muscle that can contribute to regeneration (Sampaolesi et al, 2003).…”
Section: Role Of Il-10-mediated Signalingmentioning
confidence: 99%